Optimization for squeak and rattle reduction using vibration analysis of passenger car door trim. (October 2022) - Bhosale, Omkar S; Huajre, Deepak; Laila, Murtaza S
The quality of vehicle plays an important role during the vehicle purchase. Sound quality is one of the highly ranked and commonly identified issues in automobiles. Automotive OEMs want the right-first-time design approach thus designs should be strong enough to fulfill all the criteria in terms of safety, fatigue, quality, etc. Buzz, Squeak and Rattle (BSR) are commonly classified as vehicle quality issues and marked under NVH. It is very hard to resolve BSR due to complex mechanisms and assemblies in vehicles. In this paper, the methodology is developed to reduce Rattle issues with help of shape optimization. BSR is quite unpredictable so it is hard to completely avoid it during development of overall vehicle, hence during the test run noise and its locations are marked and the focus is shifted to solving them. The methodology presented is helpful to solve the problem during the design and development phase instead of find and cure method which is currently in use. The work is limited to reducing the rattle issue in door trim and audio speaker assembly.